'Now I care': a qualitative study of how overweight adolescents managed their weight in the transition to adulthood. Issue 11 (2nd November 2016) - Sweeting, Helen; Smith, Emily; Neary, Joanne; Wright, Charlotte
Abstract : Objectives: A qualitative study of recalled experiences of early adolescent overweight/obesity revealed low levels of weight-related concern. This further analysis aimed to explore weight-related concern and weight-loss efforts as participants transitioned into adulthood. Design, participants and methods: Participants were 35 young adults from a population-based cohort study who had body mass index (BMI) >95th centile between ages 11 and 15 and participated in semistructured interviews aged 24. At age 24, they were categorised as: ' slimmers ' (N=13) who had lower BMI Z-scores at 24 than their adolescent peak and were not obese (BMI<30 kg/m 2 ); ' relapsers ' (N=8, of whom 2 were morbidly obese (BMI>35 kg/m 2 ) at age 24); ' stable ' (N=3, of whom 1 morbidly obese); and ' gainers ' (N=11, of whom 5 morbidly obese). Themes were identified and coded using NVivo qualitative data analysis software, blind to participants' current weight status. Results: Contrasting with the lack of concern recalled in respect of earlier adolescence, weight-related concerns and/or desire to lose weight generally increased around the time of school leaving and almost all participants described some form of exercise (formal/informal) and dietary weight-control strategies. Among 'slimmers', there was some (subtle) evidence of more consistent use of exercise, self-monitoring of diet and exercise and of lifestyle changes becoming habitual and/or part of identity. Few participants had accessed professional support. Diet clubs seemed to have been used most by 'gainers', some only recently. Labour-market and housing transitions were strong influences, described as facilitating weight losses by some, but increases by others. For some participants, it appeared that weight loss was simply a by-product of these transitions. Conclusions: In contrast to earlier adolescence, even the heaviest participants tended to show actual weight loss action or preparation for action. The transition to adulthood could thus be a key life stage for interventions.